Effectiveness of Science Literacy-Based Digital Teaching Materials for Disaster Mitigation Education: A Literature Review 2016-2025 - Muhammad Fadhil Khairullah; Almira Erika Putri; Rindi Sartika Dwi Oktari; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2026)
Disaster mitigation education is a strategic effort to improve students' preparedness in facing various disaster risks. The use of digital teaching materials based on scientific literacy can support students' understanding of disaster concepts and disaster preparedness. This study aims to analyze the effectiveness of digital teaching materials based on scientific literacy in disaster mitigation education through a systematic literature review approach. This study was conducted by reviewing 28 selected articles published between 2016 and 2025 through the stages of data identification, filtering, and synthesis. The results of the analysis indicate that various forms of digital teaching materials such as e-modules, Virtual Reality (VR), Augmented Reality (AR), story maps, and other interactive media can improve students' understanding of disaster concepts, scientific literacy, and disaster risk preparedness. In addition, the use of digital teaching materials also increases student engagement in the learning process and helps visualize complex scientific concepts. However, the effective implementation of digital teaching materials still faces several challenges such as limited technological infrastructure, teacher competency, and student readiness. Therefore, it is necessary to strengthen support for digital teaching materials based on scientific literacy as a learning medium in disaster mitigation education.